C-reactive protein as a potential biomarker for disease progression in dengue: a multi-country observational study - Vuong, Nguyen Lam; Rosenberger, Kerstin; Jänisch, Thomas (BMC medicine, 2020)
Dengue infection can cause a wide spectrum of clinical outcomes. The severe clinical manifestations occur sufficiently late in the disease course, during day 4-6 of illness, to allow a window of opportunity for risk stratification. Markers of inflammation may be useful biomarkers. We investigated the value of C-reactive protein (CRP) measured early on illness days 1-3 to predict dengue disease outcome and the difference in CRP levels between dengue and other febrile illnesses (OFI). We performed a nested case-control study using the clinical data and samples collected from the IDAMS-consortium multi-country study. This was a prospective multi-center observational study that enrolled almost 8000 participants presenting with a dengue-like illness to outpatient facilities in 8 countries across Asia and Latin America. Predefined severity definitions of severe and intermediate dengue were used as the primary outcomes. A total of 281 cases with severe/intermediate dengue were compared to 836 uncomplicated dengue patients as controls (ratio 1:3), and also 394 patients with OFI. In patients with confirmed dengue, median (interquartile range) of CRP level within the first 3 days was 30.2 mg/L (12.4-61.2 mg/L) (uncomplicated dengue, 28.6 (10.5-58.9); severe or intermediate dengue, 34.0 (17.4-71.8)). Higher CRP levels in the first 3 days of illness were associated with a higher risk of severe or intermediate outcome (OR 1.17, 95% CI 1.07-1.29), especially in children. Higher CRP levels, exceeding 30 mg/L, also associated with hospitalization (OR 1.37, 95% CI 1.14-1.64) and longer fever clearance time (HR 0.84, 95% CI 0.76-0.93), especially in adults. CRP levels in patients with dengue were higher than patients with potential viral infection but lower than patients with potential bacterial infection, resulting in a quadratic association between dengue diagnosis and CRP, with levels of approximately 30 mg/L associated with the highest risk of having dengue. CRP had a positive correlation with total white cell count and neutrophils and negative correlation with lymphocytes, but did not correlate with liver transaminases, albumin, or platelet nadir. In summary, CRP measured in the first 3 days of illness could be a useful biomarker for early dengue risk prediction and may assist differentiating dengue from other febrile illnesses.